Inovasi Penilaian berbasis Artificial Intelligence dengan Pendekatan Problem based Learning - Siti Nurrohmatun Nisah (Journal of Practice Learning and Educational Development, 2026)
The purpose of this study was to explore various innovations in Artificial Intelligence assessment in PBL (problem-based learning) learning in improving understanding of the basics of education and learning. This type of research uses descriptive- qualitative, primary data is taken from the basics of education and learning book, the secondary data comes from documents, articles, along with the results of research related to Ai-based assessment innovation with PBL approach. The results of this study are AI-based assessment innovations with a PBL approach in the basics of education and learning courses, in the form of an understanding test from Quiziz, namely multiple questions with a total of 10 questions and 10 scores per item. Multiple questions from qwizwhere 10 questions, with a score of 10 per item.